Outcomes of and barriers to cataract surgery in Sao Paulo State, Brazil - Ferreira, Gabriel de Almeida [UNESP]; Schaal, Luisa Fioravanti [UNESP]; Ferro, Marcela Dadamos [UNESP]; Lottelli Rodrigues, Antonio Carlos [UNESP]; Khandekar, Rajiv [UNESP]; Schellini, Silvana Artioli [UNESP] (Biomed Central Ltd, 2017)
Background: Cataract is the leading cause of blindness in developing countries and identification of the barriers to accessing treatment is essential for developing appropriate public healthcare interventions. To evaluate the barriers to cataract surgery after diagnosis and assess the postoperative outcomes in Sao Paolo State, Brazil. Methods: This prospective study evaluated cataract patients from 13 counties in Sao Paulo State in 2014. Cataract was diagnosed in the community by a mobile ophthalmic unit and patients were referred to a hospital for management. Gender, age, distance to the hospital and local municipal health structure were evaluated as possible barriers. Data were analyzed for postoperative outcomes and the impact on blindness and visual impairment. Results: Six hundred patients were diagnosed with cataract with a mean age of 68.8 +/- 10.3 years and 374 (62.3%) were females. Two hundred and fifty-four (42.3%) patients presented to the referral hospital. One hundred fortyfour (56.7%) underwent surgery, 56 (22.0%) decided not to undergo surgery, 40 (15.7%) required only YAG-Laser and 14 (5.5%) required a spectacle prescription only. Visual acuity increased statistically significantly from 1.07 +/- 0. 73 logMAR at presentation to 0.25 +/- 0.41 logMAR at the final visit after intraocular lens implantation (p=0.000). There was a statistically significantly decrease from 17 (11.8%) blind patients and 55 (38.2%) visually impaired patients at presentation to 2 (1.4%) and 5 (3.5%) patients respectively after treatment (p=0.000). Conclusion: Less than half of the individuals with cataract presented to the hospital for surgery. Among the patients who underwent treatment, there was an overall decrease in the number of blind individuals and visually impaired individuals. The barriers to cataract surgery were older age, greater distance to the hospital, municipalities with fewer inhabitants and less ophthalmic services.
Keywords: Cataract; Blindness; Treatment Outcome; Health services accessibility